Feasibility of Detecting Brain Areas Involved in Extreme Breath-Hold Diving - Jissendi-Tchofo Patrice; Jdaoudi Yassin; Germonpré Peter; Cialoni Danilo; Brizzolari Andrea; Musimu Patrick; Balestra Costantino (Journal of Neurological Research And Therapy, 2021)
A feasibility study explores neuroimaging approaches to identify brain regions engaged during extreme breath‑hold diving. Methods, safety considerations, and preliminary activation patterns are summarized to motivate further controlled studies.
Keywords: breath-hold protocol